2008
DOI: 10.1007/s11103-008-9450-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of gene expression in soybean shoot apical meristem

Abstract: The shoot apical meristem (SAM) contains undifferentiated stem cells that are responsible for the initiation of above-ground organs. The nature of genetic programs and the regulatory networks underlying SAM function in a major legume crop, soybean was investigated here. We used soybean GeneChip (containing 37,744 probe sets) to examine the transcript profiles associated with micro-dissected, actively growing SAMs or growth arrested axillary meristems (AMs) experiencing apical dominance, in comparison to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 83 publications
3
15
0
Order By: Relevance
“…To identify PEGs in these meristems (but not specifically in one of them), we grouped similar meristems together and detected 821 genes (20 paralogs). GO annotation indicated that the most enriched categories were associated with flower development and regulation, floral transition from vegetative to reproductive phase, or meristematic phase transition and transcription regulation (Figure  5, in Additional file 2: Tables S23 and S24), which is in good agreement with previous reports in soybean [50,51]. For instance, the PEGs included several homologs of SHORT VEGETATIVE PHASE ( SVP ) that specify the reproductive organ identity and control flowering time in Arabidopsis and rice [52,53] and genes involvement in WUSCHEL ( WUS ) regulatory network essential for SAM maintenance [54].…”
Section: Resultssupporting
confidence: 90%
“…To identify PEGs in these meristems (but not specifically in one of them), we grouped similar meristems together and detected 821 genes (20 paralogs). GO annotation indicated that the most enriched categories were associated with flower development and regulation, floral transition from vegetative to reproductive phase, or meristematic phase transition and transcription regulation (Figure  5, in Additional file 2: Tables S23 and S24), which is in good agreement with previous reports in soybean [50,51]. For instance, the PEGs included several homologs of SHORT VEGETATIVE PHASE ( SVP ) that specify the reproductive organ identity and control flowering time in Arabidopsis and rice [52,53] and genes involvement in WUSCHEL ( WUS ) regulatory network essential for SAM maintenance [54].…”
Section: Resultssupporting
confidence: 90%
“…The tissue was then dehydrated and embedded in paraplast (Sigma, St Louis, MO, USA) following standard methods. The in situ hybridization was carried out according to modified protocols from Jackson (1991) as described in Haerizadeh et al (2009). Observations and photography were conducted with a microscope BX60 and digital camera DP70 (Olympus, Centre Valley, PA, USA).…”
Section: In Situ Hybridization Analysismentioning
confidence: 99%
“…Recently, there has been a significant effort in understanding the genome of soybean by undertaking large‐scale genome sequencing, microarray, expressed sequence tag sequencing, and transcriptome analyses ([3, 4]; reviewed in Liew et al 2014). In addition, comprehensive studies on synteny, quantitative trait locus (QTL) mapping, and comparative genomics have increased our knowledge on soybean and closely related legumes of economic importance [58].…”
Section: Introductionmentioning
confidence: 99%